A 28-GHz Wideband 2×2 U-Slot Patch Array Antenna - Nanae Yoon; Chulhun Seo (Journal of Electromagnetic Engineering and Science, 2017)
In this study, a 28-GHz U-slot array antenna for a wideband communication system is proposed. The U-slot patch antenna structure consists of a patch, two U-shaped slot, and a ground plane. With the additional U-slot, the proposed antenna has around 10% of bandwidth at –10 dB. To increase gain, the U-slot antenna is arrayed to 2×2. The proposed antenna is designed and fabricated. The 2×2 array antenna volume is 41.3 mm × 46 mm × 0.508 mm. The proposed antenna was measured and compared with the simulation results to prove the reliability of the design. The bandwidth and gain of the measurement results are 3.35 GHz and 13 dBi, respectively and the operating frequency is around 28 GHz. KCI Citation Count: 4